2019
DOI: 10.5755/j01.ms.26.2.21374
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Tensile Properties of Single-Sided and Double-Sided Laser Welded DP600 Steel Sheets

Abstract: Dual Phase (DP) steels are the most commonly used steels in the automotive industry to reduce vehicle weight and improve car safety. DP600 steel is one of the most used steels for the automotive industry because this steel has high strength and good elongation properties. During the manufacture of automotive parts, welding is the most commonly used joining process, and especially the laser welding is getting more and more importance. This study was executed to evaluate how the welding type (single-sided and do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…In terms of mechanical properties, the optimisation of the welding parameters (laser power and pulse duration) performed in DP600 steel generated true stress values in the weld very similar to the BM (between 700 and 800 MPa), and the failures did not occur in the FZ [57]. Another investigation with same steel indicated that increases in pulse frequency led to higher tensile values [58]. In the single-sided configuration, the highest tensile strength achieved 81% of the base metal, and in the double-sided welds, the values reached up to 97%.…”
Section: Dual Phase (Dp)mentioning
confidence: 94%
“…In terms of mechanical properties, the optimisation of the welding parameters (laser power and pulse duration) performed in DP600 steel generated true stress values in the weld very similar to the BM (between 700 and 800 MPa), and the failures did not occur in the FZ [57]. Another investigation with same steel indicated that increases in pulse frequency led to higher tensile values [58]. In the single-sided configuration, the highest tensile strength achieved 81% of the base metal, and in the double-sided welds, the values reached up to 97%.…”
Section: Dual Phase (Dp)mentioning
confidence: 94%
“…Özellikle çift fazlı (DP) çelikler, üstün şekillendirilebilirlik, süneklik ve yüksek mukavemet karakteristiklerinden dolayı özellikle tercih edilmektedir. Çift fazlı çelikler ferrit matris içine dağılmış martenzit fazından oluşmaktadırlar [4][5][6][7]. Benzer ve farklı sacların birleştirilmesi günümüzde otomotiv endüstrisinde sıkça karşılaşılan bir durumdur.…”
Section: Giriş (Introduction)unclassified